Magnetic resonance imaging in Kallmann syndrome: A case report - Poudel, Shankar; Sangroula, Upama; Rajak, Ashik (Journal of Kathmandu Medical College, 2021)
Kallmann syndrome is a rare genetically inherited condition characterized by hypogonadotrophic hypogonadism and anosmia or hyposmia. It is due to failure of migration of gonadotrophic releasing hormone neuron and olfactory neuron to hypothalamus. This case reports a 39-year-old Maldivian adult with clinical features of Kallmann syndrome and magnetic resonance imaging brain showing absence of olfactory sulcus and bulb.